UPAYA MENINGKATKAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE - ELSA WIDJAJANTI NURWIJANI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
This research focuses on the implementation of the round table cooperative learning model in an effort to improve students' natural science learning outcomes, in class VIII MTsN 14 Jombang. The results of the implementation showed an increase in the learning outcomes of students in class VIII MTsN 14 Jombang from an average score of 73.83 to 78.50 and an increase in the presentation of students' mastery learning by 23.37%, from 63.35% of students who completed learning to 86 .67%. The round table type of cooperative learning model as a model that emphasizes students to play an active role, contribute, and work together in a group and listen to the views of other group members about teaching materials is proven to be able to increase the motivation of all students so that learning completeness can be achieved. ABSTRAKPenelitian ini berfokus pada implementasi Model pembelajaran kooperatif tipe round table dalam upaya meningkatkan hasil belajar IPA peserta didik, di kelas VIII MTsN 14 Jombang. Hasil pelaksanaan menunjukkan adanya peningkatan hasil belajar peserta didik kelas VIII MTsN 14 Jombang dari nilai rata rata 73,83 menjadi 78,50 dan peningkatan presentasi ketuntasan belajar peserta didik sebesar 23,37% yakni dari 63,35% peserta didik yang tuntas belajar menjadi 86,67% .Model pembelajaran kooperatif tipe round table sebagai model yang menekankan peserta didik untuk berperan aktif, berkontribusi, dan bekerjasama dalam satu kelompok serta mendengarkan pandangan dari anggota kelompok lainnya tentang bahan ajar terbukti mampu menambah motivasi seluruh siswa sehingga ketuntasan belajar bisa tercapai.